Longest sage‐grouse migratory behavior sustained by intact pathways. Issue 6 (19th May 2017) - Newton, Rebecca E.; Tack, Jason D.; Carlson, John C.; Matchett, Marc R.; Fargey, Pat J.; Naugle, David E.
ABSTRACT: Expanding human footprints across the globe are affecting animal migrations by altering their use of traditional routes and exposing them to increased costs of travel. Sustaining migratory behavior among populations requires knowledge of animal movement and space use during this critical life stage. We studied the migratory movements in a population of greater sage‐grouse ( Centrocercus urophasianus ), an imperiled species endemic to the North American sagebrush steppe, with the longest‐known obligate and annual migration for a grouse: a 240‐km journey between Saskatchewan, Canada, and north central Montana, USA. Remote tracking revealed that stepping‐stone behavior in sage‐grouse is analogous to that of migratory big game populations, which frequent stopover sites along varied and individual routes. Within migratory routes, sage‐grouse chose pathways with gently rolling grasslands and sagebrush flats. Sage‐grouse avoided cropland, making punctuated movements across a 6‐km river valley dominated by cropland and trees. During autumn migration (Oct–Nov), individuals typically spent a day at an average of 9 different stopovers while traveling 41–126 km in 14 days. Sage‐grouse were faithful to winter ranges and timing of autumn migration but demonstrated adaptive behavior in response to heavy snowfalls with no effect on survival. Birds made a mass exodus north in spring (Mar–Apr) to their respective breeding ranges, traveling up to 160 km in 18 days. Migratory pathways were stitched together by an array of public and private lands, with large and intact landscapes composed of native vegetation forming the common thread. Conservation easements and public lands policy that preclude temperate grasslands from being fragmented will be critical in maintaining the largest migratory event observed among gallinaceous species. © 2017 The Wildlife Society. Abstract : In the largest discovered migratory event by greater sage‐grouse, individuals traveled up to 240 km along international migratory pathways in a stepping‐stone fashion analogous to big game species such as mule deer. Avoidance of croplands and treed areas was the common thread among resource selection during migration, underscoring the role of intact sagebrush grasslands in maintaining this unique behavior.